2017
DOI: 10.11646/zootaxa.4272.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of Eutropis rugifera (Stoliczka, 1870) (Squamata: Scincidae) including the redescription of the holotype

Abstract: Eutropis rugifera has long been identified as a widespread species complex distributed in Nicobar, Peninsular Malaysia, Greater Sundaic Islands, Bali, Sulawesi and the Philippines. This skink was described by Stoliczka in 1870 from Nicobar Island based on a single specimen (holotype by monotypy). Later, Peters (1871), Bartlett (1895) and Werner (1896) described three more species which were morphologically similar to Euprepes percarinatus (from Java), Mabuia rubricollis (Borneo) and M. quinquecarinata (Sumatra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 513 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Our phylogeographic results are consistent with Amarasinghe et al (2017) , who recovered substantially divergent lineages on Bali and Bawean island (although they did not estimate divergence times). If we were to combine the results of Amarasinghe et al (2017) with our own (different genetic loci), it is possible that there are between three and six major clades of Sundaic E. rugifera (and potentially even more from unsampled localities): (1.) Sumatra + Nicobar Islands; (2.)…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our phylogeographic results are consistent with Amarasinghe et al (2017) , who recovered substantially divergent lineages on Bali and Bawean island (although they did not estimate divergence times). If we were to combine the results of Amarasinghe et al (2017) with our own (different genetic loci), it is possible that there are between three and six major clades of Sundaic E. rugifera (and potentially even more from unsampled localities): (1.) Sumatra + Nicobar Islands; (2.)…”
Section: Discussionsupporting
confidence: 89%
“…1 ). Barley et al (2015) and Amarasinghe et al (2017) reported E. rugifera from Sulawesi in error based on samples from the Mentawai archipelago that Barley et al incorrectly attributed to Sulawesi. Inhabiting low and mid elevation rainforests as well as peat swamps, E. rugifera is the most arboreal Eutropis on Sundaland and, although generally terrestrial, has also been found up to a height of 2 m on tree trunks ( Das, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA-barcoding techniques are now widely applied for uncovering hidden diversity in different groups of amphibians and reptiles (Smith et al 2008;Solovyeva et al 2011Solovyeva et al , 2014Che et al 2012;Nagy et al 2012;Xia et al 2012;Murphy et al 2013;Hartmann et al 2013;Amarasinghe et al, 2017;Orlova et al 2017). COI DNAbarcoding proved to be especially useful in revealing cryptic lineages within the genus Cyrtodactylus (Nazarov et al 2012Nguyen et al 2013Nguyen et al , 2014Nguyen et al , 2017Schneider et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We amplified a 653-bp fragment of cytochrome oxidase I ( COI ), a mitochondrial marker widely used as a DNA-barcoding marker for vertebrates, including reptiles and amphibians ( Murphy et al, 2013 ; Nagy et al, 2012 ; Smith et al, 2008 ), and for species identification in various groups of lizards ( Amarasinghe et al, 2017 ; Hartmann et al, 2013 ; Nazarov et al, 2012 , 2014 ; Orlova et al, 2017 Solovyeva et al, 2011 , 2014 ). We used two primer pairs for PCR and sequencing, depending on their performance in PCR, for different samples.…”
Section: Methodsmentioning
confidence: 99%